2005
DOI: 10.1142/s0219887805000491
|View full text |Cite
|
Sign up to set email alerts
|

Alignment and Algebraically Special Tensors in Lorentzian Geometry

Abstract: We develop a dimension-independent theory of alignment in Lorentzian geometry, and apply it to the tensor classification problem for the Weyl and Ricci tensors. First, we show that the alignment condition is equivalent to the PND equation. In 4D, this recovers the usual Petrov types. For higher dimensions, we prove that, in general, a Weyl tensor does not possess aligned directions. We then go on to describe a number of additional algebraic types for the various alignment configurations. For the case of second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
349
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(354 citation statements)
references
References 12 publications
4
349
0
1
Order By: Relevance
“…7 In the frame (79), from (81) one finds the only non-zero components F 1ij ∼ 1/r 2 , in agreement with (75). It may be interesting also to observe that the field (81) is self-dual (or anti-self-dual) if its only non-zero components are…”
Section: Examples For N = 6 P =supporting
confidence: 80%
See 1 more Smart Citation
“…7 In the frame (79), from (81) one finds the only non-zero components F 1ij ∼ 1/r 2 , in agreement with (75). It may be interesting also to observe that the field (81) is self-dual (or anti-self-dual) if its only non-zero components are…”
Section: Examples For N = 6 P =supporting
confidence: 80%
“…w.r.t. ℓ (i.e., decreasing alignment [7] -the G abcd term is not aligned and is thus "generic"). Similarly, for the Maxwell field one has (both for test fields in flat space [6,8,9] and for the full Einstein-Maxwell theory [6])…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, from now on we refer to the off-shell spacetime (4.1), without imposing (4.3), as to the canonical metric. The canonical metric is of the special algebraic type D [102] of the higher-dimensional algebraic classification [178], [46], [45]. Let us finally remark that formulas (4.1)- (4.3) are applicable also in D = 3 where one recovers the 2-parametric BTZ black hole [13].…”
Section: Overview Of the Kerr-nut-(a)ds Metricsmentioning
confidence: 98%
“…These solutions allow the Kerr-Schild form [185], they are of the type D of the higher-dimensional algebraic classification [178], [46], [45]. The metrics have slightly different form for the odd and even number of spacetime dimensions D. We can write them compactly as…”
Section: B1 Myers-perry Metrics and Their Symmetriesmentioning
confidence: 99%
“…, C 1i1j are subject to a number of constraints following from additional symmetries of the Weyl tensor and its tracelessness [1,2]. Boost order of a tensor T is defined as the maximum boost weight of its frame components and it can be shown that it depends only on the choice of a null direction ℓ [1,2]. Boost order of the Weyl tensor in a generic case is 2, but in algebraically special cases, there exist preferred null directions for which boost order of the Weyl tensor is less.…”
Section: Peeling Property Of the Weyl Tensormentioning
confidence: 99%